Beckman DB-GT Grating Spectrophotometer - Photomation (1960)
Produced in the 1960s, the DB-G was a single-beam grating (as opposed to a prism) ultraviolet spectrophotometer.
Keywords: Ultraviolet spectroscopy; Scientific apparatus and instruments; Spectrophotometer; Beckman Instruments, Inc.